Art law and the business of art - Wilson, Martin (Martin A. N.), 1964- (Elgar practical guides, 2022)
"In this fully revised and updated second edition of Art Law and the Business of Art, Martin Wilson, an art lawyer with more than 20 years' experience in the field, provides a comprehensive and practical guide to the application of UK law to transactions and disputes in the art world. Accessible and informative for lawyers and non-lawyers alike, this indispensable book not only outlines and explains the relevant law but also how the art business operates in practice. Chapters cover the full breadth of legal and commercial issues affecting the sale and purchase of art in various contexts, and other issues such as artists' rights in their work, import and export of artworks, art disputes, and confidentiality and data protection are all examined in detail. Wilson also offers an in-depth discussion of the most pressing ethical questions involving artworks, including Holocaust restitution, cultural heritage, and freedom of expression. New to this Edition: - Thoroughly revised guidance on new anti-money laundering requirements - Updated discussion in the context of Brexit and the impact of the Covid-19 pandemic - New coverage of the emerging issues such as the treatment of NFTs and the increased use of internet auctions This book will prove invaluable to lawyers advising on all aspects of art law and many others in the art business, including artists themselves, art dealers, and those working in auction houses and museums. It will also be crucial reading for scholars and students with an interest in art law and business"--